2022
DOI: 10.1186/s12889-022-12618-x
|View full text |Cite
|
Sign up to set email alerts
|

Are human resource managers with good listening competency more likely to avoid job burnout?

Abstract: Background Listening is an important responsibilities of human resource managers, whether it will bring role stress to human resource managers, or lead to the risk of job burnout. This study aims to analyze the impact of listening competency on job burnout among human resource managers, and examine the mediating effect of role stress. Methods This study adopted a cross-sectional method to randomly select 500 human resource managers from China’s top… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…To analyze the association between knowledge workers' job fatigue and turnover intention, a fusion layer is added to the traditional three-layer BP neural network to predict employees' turnover intention [12]. When evaluating job burnout of knowledge workers, the input function of the hidden layer is as follows [13]:…”
Section: Establish the Neural Network Model Of Employee Jobmentioning
confidence: 99%
“…To analyze the association between knowledge workers' job fatigue and turnover intention, a fusion layer is added to the traditional three-layer BP neural network to predict employees' turnover intention [12]. When evaluating job burnout of knowledge workers, the input function of the hidden layer is as follows [13]:…”
Section: Establish the Neural Network Model Of Employee Jobmentioning
confidence: 99%
“…Organisations with strong systems and well-designed management programmes are likely to experience performance improvements and improved employee engagement (Hooi, 2021). Wang and Chen (2022) also found that improved managerial competencies (such as listening skills) can help reduce role stress and mitigate the risk of burnout, while Tan et al . (2019) found that meaningful work also reduces burnout risk.…”
Section: Discussionmentioning
confidence: 99%
“…More than 15 years have been passed since the JD-R model (Demerouti et al, 2001) was completely published. As hundreds of studies of the model were conducted, it has been applied in thousands of organizations (Bakker and Demerouti, 2017;Wang and Chen, 2022). There are too numerous retrospective and meta-analysis studies to mention one by one (e.g., Crawford et al, 2010;Nahrgang et al, 2011;Bakker et al, 2014;Bakker and Demerouti, 2017), and considerable research findings have been achieved.…”
Section: Jd-r Theoretical Modelmentioning
confidence: 99%
“…Job resource may also involve physical, psychological, social, and organizational dimensions. Furthermore, job resource is able to (1) play a role in achieving the job-related goals, (2) reduce the job demand and the physical and mental costs resulting from job demand, and (3) motivate individuals to grow (Wang and Chen, 2022). The two job characteristics will lead to two kinds of psychological process.…”
Section: Jd-r Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation